Tuberculosis score chart signs and symptoms in children with positive tuberculin skin tests - Finny Fitry Yani; Rizanda Machmoed; Marhefdison Marhefdison; Darfioes Basir (Indonesian Pediatric Society, 2012)
Background The Indonesian Pediatrics Respirology WorkingGroup (IPRWG) developed the tuberculosis (TB) scorechart to assist in diagnosing TB in community health centers(Puskesmas).Objectives To document signs and symptoms of the IPRWG TBscore chart, to analyze various combinations of these signs andsymptoms, and to compare these combinations in children withTB to those without TB, based on a TB score chart.Methods We performed a cross-sectional study from July toOctober 2008, in Padang, Bukittinggi and Pasaman. We recruitedchildren with known positive tuberculin skin tests (TST) from a2006 tuberculin survey. Questionnaires on signs and symptoms(IPRWG TB score chart) were completed and chest radiographswere obtained for all children. Subjects fulfilling a total score ofsix or more were considered to have a diagnosis of TB.Results We diagnosed TB in 78/285 (27.3%) subjects. A scorevalue of3 for the category of household contact (HHC) positivesmears was added in 21/78 subjects. However, the highest risk forTB disease was found in those diagnosed with no clear history ofHHC (58.9%; OR 192, 95% CI 22 to 1679). The highest riskfactors for TB were suggestive chest X-ray (34.6%; OR 9.2, 95%CI 3.6 to 23 .4) and fever lasting > 2 weeks (17.9%; OR 8, 95%CI 2.2 to 29.1), respectively. Of 46 children with TB diagnosisbut without HHC, the combination of undernourishment, lymphnode enlargement and suggestive chest X-ray was highest (28.2%).Individual or dual combination signs and symptoms were alsofound in children without TB diagnosis.Conclusion Various combinations of signs and symptoms couldlead to fulfillment of scoring for TB diagnosis. [Paediatr lndones.2012;5 2: 78-85].